Credit unions in the South Pacific : Australia, Fiji, New Zealand, Papua and New Guinea - Runcie, Neil (London : University of London P., 1969)
This book is an interim report on developments in both the more advanced economies and some under-developed economies in the South Pacific.
Bibliography: p. [247]-249.
rpm 24/01/2019
Loans
Keywords: Credit unions